2022
DOI: 10.1002/rse2.304
|View full text |Cite
|
Sign up to set email alerts
|

A camera trap‐based assessment of climate‐driven phenotypic plasticity of seasonal moulting in an endangered carnivore

Abstract: For many species, the ability to rapidly adapt to changes in seasonality is essential for long-term survival. In the Arctic, seasonal moulting is a key life-history event that provides year-round camouflage and thermal protection. However, increased climatic variability of seasonal events can lead to phenological mismatch. In this study, we investigated whether winter-white (white morph) and winter-brown (blue morph) Arctic foxes (Vulpes lagopus) could adjust their winter-to-summer moult to match local environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 96 publications
(145 reference statements)
0
1
0
Order By: Relevance
“…Various studies have found camera traps to be an ideal tool for establishing the effectiveness of animal crossings on highways, improving multi-species landscape connectivity 17 , testing corridor models 18 and assessing the effects of forest fragmentation on diversity 19,20 . Camera traps have also been used to assess the adaptability of arctic foxes (Vulpes lagopus) in Norway to local environmental conditions to determine whether they are able to adapt their moult from winter to summer 21 . Camera traps are also used to establish the complex ecological interactions between animal behavior and climate change 2,20 .…”
Section: Monitoring In Zoology Using Camera Trapsmentioning
confidence: 99%
“…Various studies have found camera traps to be an ideal tool for establishing the effectiveness of animal crossings on highways, improving multi-species landscape connectivity 17 , testing corridor models 18 and assessing the effects of forest fragmentation on diversity 19,20 . Camera traps have also been used to assess the adaptability of arctic foxes (Vulpes lagopus) in Norway to local environmental conditions to determine whether they are able to adapt their moult from winter to summer 21 . Camera traps are also used to establish the complex ecological interactions between animal behavior and climate change 2,20 .…”
Section: Monitoring In Zoology Using Camera Trapsmentioning
confidence: 99%